2017
DOI: 10.4236/as.2017.810082
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping Empower Reduces Insect Pests and Increases Biodiversity in Agro-Ecosystem

Abstract: Currently insect pest management solely depends on chemical pesticide that continuously affects on environment, biodiversity, animal as well as human health. Outbreak of secondary insect pest is also the cost of pesticide use in field leading crop more vulnerable to more pests. These negative impacts of pesticides have provoked growing interest in the adoption of multi-function agricultural biodiversity that promote pest management, creating interesting challenge for traditional approaches to regulatory compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 29 publications
(18 reference statements)
0
7
0
1
Order By: Relevance
“…High numbers of parasitoids were recorded in push–pull and maize-cowpea intercrop plots as opposed to maize sole cropping systems ( Mudare et al, 2022 ). Other research found that a large number of parasitoids in maize-legume intercropping systems correlates with a high level of biodiversity ( Afrin et al, 2017 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“…High numbers of parasitoids were recorded in push–pull and maize-cowpea intercrop plots as opposed to maize sole cropping systems ( Mudare et al, 2022 ). Other research found that a large number of parasitoids in maize-legume intercropping systems correlates with a high level of biodiversity ( Afrin et al, 2017 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“…Water stressed condition reduced the fecundity of several sap feeder including aphids when soil water regimes decreased from 8 to 2% [18], tiny sap feeders face difficulties to get concentrated cell sap with low cell turgidity. Afrin et al [19] reported that intercropping mustard with garlic, onion and coriander significantly reduced aphid population trough acted as repellents. Boarder crop like maize and sorghum may be utilised to reduce the dispersal of the sucking pest like jassid, whitefly, shoot fly etc.…”
Section: Cultural Managementmentioning
confidence: 99%
“…Commercial monoculture farming systems are highly dependent on external inputs (synthetized fertilizers, chemical pesticides, and growth regulators) with simplified ecosystems (Kremen, Iles, & Bacon, ; Malézieux, ). In contrast, agricultural systems that promote functional biodiversity and support ecological processes allow for benefits from many ecosystem services, such as nutrient cycling, soil structuration, and pest control (Afrin et al, ; Altieri & Rosset, ; Zhang, Werf, Zhang, Li, & Spiertz, ).…”
Section: Ecosystem Invasibility and Integrated Pest Managementmentioning
confidence: 99%